An application of multi-variate analysis in hydrology - Yevjevich, Vujica M., 1913-, author; Dhyr-Nielsen, M., author; Schulz, Edmund F., author; Environmental Resources Center, Colorado State University, publisher (Colorado State University. Libraries, 1972)
Multivariate analysis was used to make a selection of some of the more meaningful physical parameters dealing with the response of a small watershed to flood producing rainfall. Factor Analysis, Principal Component Analysis and a Correlation Coefficient Matrix was utilized. The list of 24 parameters was reduced to a list of 8 parameters. This reduction results in a very material economy in the encoding of relevant geomorphological data in flood analysis.
CER72-73VY-MD-EFS3.
August 31, 1972.
Submitted to the Office of Water Research and Technology, U. S. Department of the Interior.
Circulating copy deaccessioned 2020.
Keywords: Hydrology -- Mathematical models; Watersheds -- Mathematical models